EFFECT OF NIGERIA’S COMMUNITY ACTION FOR RESILIENCE AND ECONOMIC STIMULUS (NG-CARES) PROGRAMME ON MAIZE FARMERS INCOME IN JIGAWA AND KANO STATES, NIGERIA - Ibrahim, F.; Ebenehi, O.; Tijjani, A.R. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study assessed the effect of NG-CARES programme on maize farmers’ income in Kano and Jigawa States, Nigeria. A multi-stage sampling method was used to select 260 beneficiaries and 260 non-beneficiaries, making a total of 520 respondents from six Local Government Areas in the two states. Data were collected with the aid of well-structured questionnaire and analyzed using descriptive statistics and Propensity Score Matching (PSM). The findings revealed that the beneficiaries were mainly middle-aged farmers, with a mean age of 49.38 years. They had large households, with a mean of 13 people, and small farms, with a mean of 1.45 hectares. The programme has demonstrated significant effect on the income of its beneficiaries with an ATT of ₦151,720.93 and an ATU of ₦144,906.667 and an ATE of ₦148,546.584 which reflects what the non-beneficiaries would have earned had they benefitted from the programme. Which was statistically significant at (p<0.01). The study concluded that the NG-CARES programme significantly improved the income of the maize farmers in the study area The study recommends the need for sustaining the programme since it made such significant impact on the livelihood of its target beneficiaries.